Palaeo-moisture evolution in monsoonal Central Asia during the last 50,000 years - Herzschuh, Ulrike (Prof. Dr.) (Quaternary Science Reviews, 2006)
The late-Quaternary climate history of monsoonal Central Asia was inferred from 75 palaeoclimatic records which provide information about moisture conditions in the last 50 ka (or part of this period). Wet conditions occurred during middle and late Marine Isotope Stage 3, while the Last Glacial Maximum (LGM) was characterized by dry climate conditions in the region. A stepwise climate amelioration is suggested by the climate records following the LGM. Several climate signals of this period, which were reported from high-latitude ice core records, are preserved in archives from monsoonal Central Asia as well. During the early Holocene, high effective moisture was inferred from most records from the area dominated by the Indian Monsoon (e.g. the Tibetan Plateau) suggesting that Holocene optimal climate conditions occurred there during this period. In contrast, areas which are dominated by the South-East Asian monsoon (SE Monsoon) and the Westerlies (in north-western and north-central China, Mongolia) do not uniformly show an early Holocene climate optimum. For this area optimal conditions prevailed during the mid-Holocene. These apparent contradictions can possibly be explained by the regional uplift and descent of air masses in the Holocene. During the early Holocene, strengthened insolation possibly caused an enhanced low-level convergence over the Tibetan Plateau which led to the intensification of the summer monsoon. The strong air uplift caused intensified precipitation and air divergence in the upper troposphere over the Tibetan Plateau. The areas adjacent to the north therefore experienced an intensified descent of air masses and consequently increased aridity. The majority of the palaeoclimatic records suggest reduced effective moisture since the late Holocene in the region.